MRI and FDG-PET in the assessment of inflammatory aortic arch syndrome in complicated courses of giant cell arteritis. Issue 7 (26th January 2008) - Both, M; Ahmadi-Simab, K; Reuter, M; Dourvos, O; Fritzer, E; Ullrich, S; Gross, W L; Heller, M; Bähre, M
Abstract : Objectives: To evaluate the use of MRI and FDG-PET for the diagnosis and measurement of disease activity of inflammatory aortic arch syndrome in patients with complicated giant cell arteritis. Methods: MRI and FDG-PET were performed for 25 patients with giant cell arteritis who presented with a complicated disease course despite immunosuppressive therapy. Disease activity of the thoracic aorta and the supra-aortic arteries as assessed by both modalities was compared with serological (C-reactive protein (CRP), erythrocyte sedimentation rate (ESR)) and clinical findings (Birmingham vasculitis activity score (BVAS.2)). Additionally, the usefulness of MRI for assessment of vessel wall thickening, aneurysms and stenoses was evaluated. Results: In 17/25 patients, MRI disclosed structural vessel lesions suspicious for vasculitis. Active disease was detected by MRI, thoracic PET, and whole body PET in 22, 14 and 20 patients, respectively. While serological and clinical findings correlated significantly with each other, there was no concordance with MRI and only low, non-significant correlation of PET with CRP ( r s  =  −0.158, 0.136), ESR ( r s  =  −0.232, 0.320) and BVAS.2 ( r s  =  −0.064, 0.221) for disease activity. Conclusions: MRI and PET are unreliable for assessing large-vessel inflammation in patients with giant cell arteritis and pre-existing immunosuppressive therapy. MRI is valuable for its ability to detect morphological vessel lesions, such as aneurysms and stenoses.